IL-7: A promising adjuvant ensuring effective T cell responses and memory in combination with cancer vaccines? - Zhao, Yue; Wei, Kongyuan; Chi, Hao; Xia, Zhijia; Li, Xiaosong (Frontiers in Immunology, 2022)
Cancer vaccines exhibit specificity, effectiveness, and safety as an alternative immunotherapeutic strategy to struggle against malignant diseases, especially with the rapid development of mRNA cancer vaccines in recent years. However, how to maintain long-term immune memory after vaccination, especially T cells memory, to fulfill lasting surveillance against cancers, is still a challenging issue for researchers all over the world. IL-7 is critical for the development, maintenance, and proliferation of T lymphocytes, highlighting its potential role as an adjuvant in the development of cancer vaccines. Here, we summarized the IL-7/IL-7 receptor signaling in the development of T lymphocytes, the biological function of IL-7 in the maintenance and survival of T lymphocytes, the performance of IL-7 in pre-clinical and clinical trials of cancer vaccines, and the rationale to apply IL-7 as an adjuvant in cancer vaccine-based therapeutic strategy.